Análise crítica de discursos sobre produção de textos argumentativos em livros didáticos de Língua Portuguesa - Stefanello, Claridiane de Camargo (2019)
This research aims to analyze the discourse (s) on recurrent argumentative texts production in the Português Linguagens (Portuguese Languages) collection, 9th Edition of the year 2015, by William Roberto Cereja and Thereza Cochar Magalhães of Middle School. The theoretical framework adopted is based on the perspective of Critical Discourse Analysis (FAIRCLOUGH, 2001), in the Systemic- Functional Linguistics theory (HALLIDAY, 1989, 1994, HALLYDAY and MATTHIESSEN, 2004) and in the Theoretical Perspectives of Argumentation. The corpus comprises the units and sections of textual production that aim to teach the production of argumentative texts directed from the 6th to the 9th grade of Middle School. The analysis contemplates: i) the contextual analysis of the Textbook in Brazil, focusing on the PNLD of Portuguese Language and a specific look at the general description of the Português Linguagens collection and sections devoted to textual production; and ii) the textual analysis, initially focusing on the description of the selected Units based on the semantic categories and the Transitivity System. In contextual analysis, we critically describe the production and circulation context of the collection and confirm the impact of the approval and distribution of the material in the Brazilian school context, since it has been selected for sixteen years. We also seek to know the PNLD Guide (2017-19) in order to understand the process of how publishers seek to contemplate the criteria established by the program for the collections to be approved. In relation to the collection, specifically the section on Production of Texts, we note the importance attributed to the axis of textual production, corroborating the guidelines in the PNLD Guide (2017-19) at a time when it highlights the topics of reading, production of written texts, orality and linguistic knowledge. We also identify the predominance of the literary and advertising spheres, which confirms to some extent a discourse that delegitimizes a possible discursive change that involves the presence of unrecorded genres and spheres in textbooks, since the argumentative genres appear in smaller numbers, revealing that the production of argumentative texts does not constitute the main objective of Middle School. In the textual analysis, we verify the types of processes present in the categories of the section of textual production in the light of the Transitivity System. The Material Processes refer to the occasions of the practical experience of a new activity, directing itself to the sense of doing and happening, of action. That is, they indicate an action to the students, whose objective is to produce an argumentative text. Now, the Relational Processes serve to characterize and identify the genre. In addition, we verified the predominance of a discourse to produce argumentative texts of Argumentation as a new rhetoric, since the didactic material values the context of production and reception of the texts, as already identified by the PNLD Guide. The analysis indicates that there is no systematic teaching of genre or argumentation and, therefore, there is a need to reconstruct activities, observing the concept of the genre, its linguistic and discursive characteristics, for example. From the analysis of the data, we conclude that the possible difficulties of writing argumentative texts can be motivated by the lack of a systematic teaching of argumentative texts in a discursive genre perspective in Middle School, since to a large extent the Textbook is the only one teacher's work tool.